Kajian Tentang Tingkat Pemahaman Masyarakat Terhadap Sistem Perbankan Syariah - Apria Nasrullah Imrani Mahfudz (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Despite the progress made by Islamic banks, they still contend with the dominance of conventional banking, which implements an interest-based system. This study aims to assess the public's understanding of Islamic banking, particularly in Jakarta. Field research conducted in the capital city revealed that while people are aware of the existence of Islamic banks, their understanding of the intricacies remains limited. Many are unfamiliar with the products and services offered by Islamic banks, attributing this to a lack of information disseminated through various media channels. This study sheds light on the challenges Islamic banks face in raising public awareness and understanding.